Mammadova, Aygun - (:unkn) unknown (My University, 2026)
Aygun Jahan Mammadova, PhD in Philology, Associate Professor, is the Head of the Department of Foreign Languages at the Azerbaijan University of Architecture and Construction (AzUAC). She earned her Bachelor's and Master's degrees from Azerbaijan University of Languages and received her PhD in Philology in 2010. Her research interests include English language teaching methodology, English for Academic Purposes (EAP), applied linguistics, artificial intelligence in education, educational technologies, quality assurance in higher education, and foreign language instruction for engineering and technical specialties. She is the author and co-author of more than 80 scientific and educational publications, including journal articles, conference papers, textbooks, educational manuals, and glossaries. She has participated in numerous international research and professional development programmes in Europe and the United States and was awarded the "Leading Education Figure of the Republic of Azerbaijan" badge by the Ministry of Science and Education. Her recent publications include the textbook Cultural Heritage: Azerbaijan and Uzbekistan (2026).